Heteromysis cocoensis n. sp. (Crustacea: Mysida: Mysidae) from coastal waters of Isla del Coco, Costa Rica - Price, W. Wayne (2018)
A survey of the invertebrate fauna of coral reef hard bottom communities in the shallow waters of Isla del Coco yielded a new species of mysid belonging to the genus Heteromysis S. I. Smith, 1873. Heteromysis (Olivemysis) cocoensis, n. sp. was collected from coral rubble at depths of 8 to 34 m. It differs from its congeners by having male pleopods 1, 3, and 4 with modified setae. Within the subgenus Olivemysis Băcescu, 1968, the new species is morphologically most similar to Heteromysis. ekamako Wittmann and Chevaldonne, 2017 from the Pacific, Heteromysis. gomezi Băcescu, 1970, H. mayana Brattegard, 1970, and H. rubrocinta, Băcescu, 1968 from the Western Atlantic, and Heteromysis. dardani Wittmann, 2008, Heteromysis. wirtzi Wittmann, 2008, and Heteromysis. sabelliphila Wittmann and Wirtz, 2017 from the Eastern Atlantic. However, H. cocoensis n. sp. is distinguished from these six apparently closely related species by the following combination of characters: flagellate, modified setae on articles 1 and 3 of the antennular peduncle, and setation of thoracic endopod 3, male pleopods 1, 3 and 4, uropodal endopods, and the apical and lateral margins of the telson. A diagnostic table separating these eight species is given.